Economic valuation of conservation of living heritage in Melaka City, Malaysia - Chiam, Chooi Chea (2013)
Melaka living heritage is a unique living testimony to the multi-cultural heritage and tradition of Asia from the past with great national and international significance, recognized by UNESCO as World Heritage Site in year 2008. Melaka is located at the southern part of Peninsular Malaysia bearing economic functions as a surviving historic city of the country. Despite the great opportunities for conserving the living heritage in Melaka, the city is currently facing threats of high traffic, excessive depletion of the natural environment in the city. This is due to underestimation on the non-market values of living heritage in development decisions. The aim of this study is to estimate the economic benefit of living heritage in Melaka city as the results would be able to provide insight to the value of this unique heritage to the society. The methods employed are Contingent Valuation Method Single-Bounded (Single-Bounded CVM), Contingent Valuation Method Double-Bounded (Double-Bounded CVM) and Choice Experiment (CE). The payment vehicle opted in this study is via accommodation, where a fixed heritage charge per night was included in the total accommodation bill in Melaka. In CVM, the logit model was defined based on dichotomous choice method to estimate the willingness-to-pay (WTP) randomly with five different starting bid value (RM3/RM4/RM5/RM6/RM7). Meanwhile, in CE, four attributes of non-market value of the city were defined; living heritage, natural environment, crowded recreational activities and heritage charge value. A total of 502 respondents were interviewed in person, using random stratified sampling method. The results demonstrated positive WTP for living heritage conservation by the respondents in this study. The findings also indicated that respondents who are married and of foreign nationality were more likely to pay for the living heritage conservation. The estimated mean for the WTP was RM3.70 per night from single-bounded CVM andM RM5.60 per night from double-bounded CVM. While in CE, the attribute for crowded recreational activities in the city provides the highest probability for the respondents for this study to pay for an improvement level. While living heritage attribute has a negative probability of the respondents to pay for a higher level of this attribute. The findings of this study can provide useful information to policy-makers, Majlis Bandaraya Melaka Bersejarah (MBMB), public and communities to better consideration of the consequences of present policies on the real value of living heritage in the city. Besides that, the results of valuation can help to convince the government and other decision makers to allocate more resources for conservation. Quantifying the major benefits provided by living heritage can provide invaluable support to the conservation efforts and the WTP results could encourage policy-makers to set priorities to ensure that the living heritage would be conserved in proper manner.